On autotopies and automorphisms of n-ary linear quasigroups - Marini, A.; Shcherbacov, V. (Algebra and Discrete Mathematics, 2004)
In this article we study structure of autotopies,
automorphisms, autotopy groups and automorphism groups of nary linear quasigroups.
We find a connection between automorphism groups of some
special kinds of n-ary quasigroups (idempotent quasigroups, loops)
and some isotopes of these quasigroups. In binary case we find
more detailed connections between automorphism group of a loop
and automorphism group of some its isotope. We prove that every
finite medial n-ary quasigroup of order greater than 2 has a nonidentity automorphism group.
We apply obtained results to give some information on automorphism groups of n-ary quasigroups that correspond to the ISSN
code, the EAN code and the UPC code.